Effectiveness of pertussis vaccination in pregnancy to prevent hospitalisation in infants aged <2 months and effectiveness of both primary vaccination and mother's vaccination in pregnancy in infants aged 2-11 months. Issue 44 (19th October 2022) - Merdrignac, Lore; Acosta, Lesly; Habington, Adele; Garcìa Cenoz, Manuel; Pandolfi, Elisabetta; Fabiánová, Kateřina; Jordan, Iolanda; O'Sullivan, Niam; Navasués, Ana; Tozzi, Alberto E.; Zavadilová, Jana; Jané, Mireia; et al.
Highlights: PERTINENT is a European active hospital-based surveillance system for pertussis in infants. We measured the effectiveness of maternal and primary vaccination in infants <2 and 2–11 months. Maternal vaccination reduced severe pertussis incidence in infants too young for vaccination. Infants' vaccination reduced severe pertussis irrespective of the mother's vaccination status. Only network allowing for independent multi-country pertussis vaccine effectiveness studies. Abstract: Background: PERTINENT is an active hospital-based surveillance system for pertussis in infants. In 2019, four of the six participating European countries recommended pertussis vaccination in pregnancy. Among infants aged <2 months, we measured the vaccine effectiveness (VE) in pregnancy; among infants aged 2–11 months, VE of vaccination in pregnancy and of primary vaccination (PV). Methods: From December 2015 to 2019, we included all infants aged <1 year presenting with pertussis-like symptoms. Using a test-negative-design, cases were infants testing positive for Bordetella pertussis by PCR or culture. Controls were those testing negative for all Bordetella species. Vaccinated mothers were those who received vaccine in pregnancy. Vaccinated infants were those who received ≥1 dose of PV > 14 days before symptom onset. We excluded infants with unknown maternal or PV status or with mothers vaccinated ≤14 days before delivery. We calculated pooled VE as 100 * (1-odds ratio of vaccination) adjusted for study site, onset date in quarters and infants' age group. Results: Of 829 infants presenting with pertussis-like symptoms, 336 (41%) were too young for PV. For the VE in pregnancy analysis, we included 75 cases and 201 controls. Vaccination in pregnancy was recorded for 9 cases (12%) and 92 controls (46%), adjusted VE was between 75% [95%CI: 35–91%] and 88% [95%CI: 57–96%]. Of 493 infants eligible for PV, we included 123 cases and 253 controls. Thirty-one cases and 98 controls recorded both PV with ≥ 1 dose and vaccination in pregnancy, adjusted VE was between 74% [95%CI: 33–90] and 95% [95%CI: 69–99]; 27 cases and 53 controls recorded PV only, adjusted VE was between 68% [95%CI: 27–86] and 94% [95%CI: 59–99]. Conclusion: Our findings suggest that vaccination in pregnancy reduces pertussis incidence in infants too young for PV. In infants aged 2–11 months, PV only and both PV and vaccination in pregnancy provide significant protection against severe pertussis.